Pengaruh Media Video Terhadap Pengetahuan Dan Sikap Ibu Hamil Tentang Anemia Di Wilayah Kerja Puskesmas Nanggulan Kabupaten Kulon Progo - Ridwan Febrianta; I Made Alit Gunawan; Almira Sitasari (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2019)
Anemia in pregnancy can have a negative impact on mortality and morbidity of mother and fetus. The results of pregnancy with anemia among intra-uterine growth retardation (IUGR), preterm birth, low birth weight (LBW), and an increased risk of neonatal death. Effect of pregnancy on maternal anemia among shortness of breath, fatigue, palpitations, sleep disturbances, increased risk of bleeding during labor, pre-eclampsia, and sepsis.To determine the effect of video media to the knowledge and attitude in preventing anemia among pregnant mothers.Quasi-experimental research design with pre-post test with control group design. The research was conducted from April to May 2019 in Puskesmas Posyandu Nanggulan. The sample collection with purposive sampling, wherein each a group treatment minimum of 18 samples. The independent variable was nutrition counseling media used video and powerpoint. The dependent variable is the knowledge and attitude of pregnant women. The analysis by paired sample and independent sample t test.From the test results free sample there are significant differences in the results of knowledge with p = 0.001 and attitudes with p = 0.006. Then the sample is bound to increase in knowledge and attitudes are significant in the treatment group in the form of video media compared with the control group in the form of powerpoint with p = 0.000.There was an increase in knowledge and attitude of pregnant women significantly after being consulted using video media about anemia problem.